Determination of tellurium at ultratrace levels in drinking water by on-line solid phase extraction coupled to graphite furnace atomic absorption spectrometer - Pedro, Juana (2008)
In this paper, two time-based flow injection (FI) separation pre-concentration systems coupled to graphite furnace atomic absorption spectrometry (GFAAS) for tellurium determination are studied and compared. The first alternative involves the pre-concentration of the analyte onto Dowex 1X8 employed as packaging material of a micro-column inserted in the flow system. The second set-up is based on the coprecipitation of tellurium with La(OH)3 followed by retention onto XAD resins. Both systems are compared in terms of limit of detection, linear range, RSD%, sample throughput, micro-columns lifetime and aptitude for fully automatic operation. The features of the Dowex system are: 37% efficiency of retention and an enhancement factor of 42 for a pre-concentration time of 180 seconds (sample flow rate=3 ml min-1) with acetic acid elution volumes of 80 µl. The detection limit (3 s) is 7 ng l-1 and the relative standard deviation (n=7200 ng l-1) is 5.8%. The analytical performance of the XAD system is: 72% efficiency of retention and an enhancement factor of 25 for a pre-concentration time of 180 s (sample flow rate=3 ml min-1) with nitric acid elution volumes of 300 µl. The detection limit is 66 ng l-1 and the relative standard deviation (n=7200 ng l-1) is 8.3%. Applications to the determination of tellurium in tap water and the validation of the analytical methodology employing SRM 1643e as certified reference material are shown.